Bilevel positive airway pressure improves the autonomic balance in the postoperative period following cardiac surgery: a randomized trial - Antônio Marcos Vargas da Silva; Angélica Trevisan de Nard; Geovana de Almeida Righi; Juliana Rosa Nascimento; Raysa Maldonado Lima; Luis Ulisses Signori (Universidade de São Paulo, 2022)
ABSTRACT The use of bilevel positive airway pressure (BiPAP) has repercussions on cardiorespiratory outcomes. However, the literature still lacks analyses of the postoperative influence of BiPAP on the modulation of the autonomic nervous system after cardiac surgery. This study aimed to evaluate the effects of BiPAP on peripheral oxygen saturation, vital signs, and autonomic balance during hospitalization after cardiac surgery. This randomized controlled trial evaluated 36 patients before and after surgery. The BiPAP group was treated in two 20-minute daily sessions of routine physical therapy since 18 hours after surgery until discharge. The control group received routine physical therapy during the same period. Our primary outcome was peripheral oxygen saturation. Secondary outcomes were vital signs and autonomic balance evaluated by heart rate variability. We observed that peripheral oxygen saturation and blood pressure were unaffected at hospital discharge. Both groups showed a similar increase in heart and respiratory rates. The BiPAP group showed a reduction of the low sympathetic frequency component in −27.1 n.u. (95% CI: −39 to −15.2), increase of high parasympathetic frequency in 27.1 n.u. (95% CI: 15.2 to 39), and an improvement to the LF/HF ratio in −2.5 (95% CI: −3.8 to −1.2), when compared to the control group. BiPAP attenuated sympathetic activity and improved vagal modulation and autonomic balance at hospital discharge. These findings evidence that BiPAP enables more efficient autonomic mechanisms during hospitalization after cardiac surgery.